2021
DOI: 10.1007/s40675-021-00210-5
|View full text |Cite
|
Sign up to set email alerts
|

The Link Between Obstructive Sleep Apnoea and Neurodegeneration and Cognition

Abstract: Purpose of Review Obstructive sleep apnoea (OSA) is increasingly found to have an impact on neurodegeneration. In this review, we summarise recent findings on the association between OSA and brain morphology, cognition, and processes related to Alzheimer’s dementia (AD) and Parkinson’s disease (PD). Recent Findings Associations between OSA and alterations in grey and white matter, brain diffusivity, and deficits in memory, attention, and executive control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Sleep apnea is strongly associated with cognitive deficits (40,76) with nocturnal hypoxemia closely linked to impaired memory performance (77). While sleep apnea and cognitive decline may co-occur as part of an underlying neurodegenerative illness (78,79), cognitive deficits may also be secondary to or aggravated by sleep apnea (76,80,81). This picture fits with the Cluster 3 we identified, which included people with greater sleep apnea severity and reduced memory performance (although not as severe as Cluster 2).…”
Section: Discussionsupporting
confidence: 68%
“…Sleep apnea is strongly associated with cognitive deficits (40,76) with nocturnal hypoxemia closely linked to impaired memory performance (77). While sleep apnea and cognitive decline may co-occur as part of an underlying neurodegenerative illness (78,79), cognitive deficits may also be secondary to or aggravated by sleep apnea (76,80,81). This picture fits with the Cluster 3 we identified, which included people with greater sleep apnea severity and reduced memory performance (although not as severe as Cluster 2).…”
Section: Discussionsupporting
confidence: 68%
“…This suggests that these vascular risk factors may account for considerable variance in the relationship between clinical ADHD and 10-year dementia risk; additional prospective longitudinal studies will be needed to validate these findings in adults across the ADHD symptom severity spectrum, with richer cognitive and behavioural outcomes. Further, there has been increasing recognition of other medical and physical conditions in ADHD 12 , 76 that were not examined here but that may also contribute to cognitive changes into later adulthood, such as liver disease 77 , epilepsy 78 and obstructive sleep apnea 79 . These conditions should be explored as potential mediators in future work.…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be a synergistic relationship between sleepdisordered breathing and Alzheimer's disease because they share certain etiological and physiopathological determinants that predispose them to the development of both disorders in the same patient (Figure 2) [34,82]. First, the presence of OSA, sleep fragmentation, and nocturnal hypoxia are linked with higher cognitive impairments such as decreased memory, attention, and executive function [83][84][85][86], symptoms inherent in AD. Furthermore, it was found that the more severe the form of OSA, the stronger the association between the apnea-hypopnea index, the oxygen desaturation index, and the prediction of memory impairment [87].…”
Section: Bidirectional Relationship Between Obstructive Sleep Apnea A...mentioning
confidence: 99%